2014
DOI: 10.1149/2.103406jes
|View full text |Cite|
|
Sign up to set email alerts
|

Alcohol-Aminosilicate Hybrid Coatings for Corrosion Protection of Galvanized Steel in Mortar

Abstract: Organic-inorganic hybrid (OIH) matrices were synthesized by sol-gel method and deposited on hot-dip galvanized steel (HDGS) using a dip-coating process. These OIHs, generally called amino-alcohol-silicates, were synthesized using a functionalized siloxane, 3-glycidoxypropyltrimethoxysilane, and five oligopolymers (Jeffamine) with different molecular weights: 230, 400, 600, 900 and 2000. Besides the five different pure OIH matrix coatings, a similar set of HDGS samples were coated with the OIH matrices doped wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 46 publications
4
38
0
Order By: Relevance
“…In many instances, a dry gel needs further thermal treatment to be densified [20]. The sol-gel process versatility allows incorporation of additional components that introduce material's complementary functionalities, such as UV protection [21,22], anti-fouling [23,24], anti-reflection [25][26][27][28][29], moisture resistance [29][30][31][32][33], corrosion and adhesion protection [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53], along with the enhancement of mechanical, thermal, and optical properties, opening a wide range of application in several fields of science. Furthermore, this method allows the control of several experimental conditions leading to a simple sequence that may be tuned to the nature, final shape, and desired function.…”
Section: General Background Of Sol-gel Coatings For Corrosion Mitigationmentioning
confidence: 99%
See 1 more Smart Citation
“…In many instances, a dry gel needs further thermal treatment to be densified [20]. The sol-gel process versatility allows incorporation of additional components that introduce material's complementary functionalities, such as UV protection [21,22], anti-fouling [23,24], anti-reflection [25][26][27][28][29], moisture resistance [29][30][31][32][33], corrosion and adhesion protection [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53], along with the enhancement of mechanical, thermal, and optical properties, opening a wide range of application in several fields of science. Furthermore, this method allows the control of several experimental conditions leading to a simple sequence that may be tuned to the nature, final shape, and desired function.…”
Section: General Background Of Sol-gel Coatings For Corrosion Mitigationmentioning
confidence: 99%
“…Organic inhibitors derived from thiazole [103,107,122,129] have also shown quite good results. However, it has been reported that the presence of inhibitors within the sol-gel coating, namely, when freely dispersed in the hybrid matrix, above a certain limit, has a detrimental effect in the long-term chemical stability and barrier properties of the coatings [43,44,121]. Consequently, several research efforts in this field have been focused on the development of micro-and nanocontainers compatible with hybrid sol-gel coatings that can be used for the controlled storage and release of the corrosion inhibitor ( Figure 9) [39,40,[130][131][132][133][134][135][136][137][138][139][140][141].…”
Section: Corrosion Protective Sol-gel Coatings In Aluminium Substratesmentioning
confidence: 99%
“…These OIHs, generally called ureasilicates [29] U(X) and amino-alcohol-silicates [30] A(X) were obtained using two different functionalised siloxanes: 3-Isocyanatopropyltriethoxysilane and 3-Glycidoxypropyltrimethoxysilane. Each functionalised siloxane was made to react with five oligopolymers (referred to as Jeffamine) with different molecular weights (MWs): 230, 400, 600, 900 and 2000.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decades, EIS has been widely used for coatings characterization [119,120,[193][194][195][196][197][198][199][200][201][202]. EIS is a transient technique where a sinusoidal signal (potential) is applied with low amplitude, to not disturb the equilibrium conditions of the system.…”
Section: Electrochemical Impedance Spectroscopy Methods (Eis)mentioning
confidence: 99%
“…In the last few decades, several types of organic-based coatings have been developed [85], including anti-fouling paints [70,[86][87][88][89][90][91][92][93][94], composites and nano-coatings [94][95][96], self-healing coatings [97][98][99][100][101][102][103][104][105][106][107], and hybrid sol-gel materials [98,[108][109][110][111][112][113][114][115][116][117][118][119][120][121] among others. However, as far as the authors' knowledge, very few studies were performed on OWSs using self-healing and hybrid sol-gel coatings.…”
Section: Coating Systemsmentioning
confidence: 99%